Spectrum of technetium-99m methylene diphosphonate (99mTc MDP) uptake in Osteosarcoma - Gill, Sana Munir; Sadaf Mufty; Aamna Hassan (Journal of the Pakistan Medical Association, 2023)
Osteosarcoma is a frequently occurring primary skeletal malignancy in the adolescent population. It arises from primitive mesenchymal bone forming cells and frequently involves long bones near the metaphyseal growth plate. Multiple imaging modalities are used for complete staging workup at the time of presentation; including magnetic resonance imaging (MRI) for local disease extent, computed tomography (CT) scan to rule out pulmonary metastasis, and bone scan to look for distant osseous metastases. We present the case of a young boy with osteosarcoma of left tibia, showing additional findings on MDP bone scan acquired for initial staging work up. Key words: Osteosarcoma, bone scan, calcified nodal metastases, SPECT/CT